Myogenin promotes myocyte fusion to balance fibre number and size. Issue 1 (December 2018) - Ganassi, Massimo; Badodi, Sara; Ortuste Quiroga, Huascar; Zammit, Peter; Hinits, Yaniv; Hughes, Simon
Abstract Each skeletal muscle acquires its unique size before birth, when terminally differentiating myocytes fuse to form a defined number of multinucleated myofibres. Although mice in which the transcription factor Myogenin is mutated lack most myogenesis and die perinatally, a specific cell biological role for Myogenin has remained elusive. Here we report that loss of function of zebrafishmyog prevents formation of almost all multinucleated muscle fibres. A second, Myogenin-independent, fusion pathway in the deep myotome requires Hedgehog signalling. Lack of Myogenin does not prevent terminal differentiation; the smaller myotome has a normal number of myocytes forming more mononuclear, thin, albeit functional, fast muscle fibres. Mechanistically, Myogenin binds to themyomaker promoter and is required for expression ofmyomaker and other genes essential for myocyte fusion. Adultmyog mutants display reduced muscle mass, decreased fibre size and nucleation. Adult-derivedmyog mutant myocytes show persistent defective fusion ex vivo. Myogenin is therefore essential for muscle homeostasis, regulating myocyte fusion to determine both muscle fibre number and size. Loss of the transcription factor Myogenin in mice reduces skeletal myogenesis and leads to perinatal death but how Myogenin regulates muscle formation is unclear. Here, the authors show that zebrafish Myogenin enhances Myomaker expression, muscle cell fusion and myotome size, yet decreases fast muscle fibre number.